La carte sanitaire à l’épreuve des pratiques sanitaires des citadins - Maud Harang Cisse (Territoire en Mouvement)
Since the WHO conference of Harare (Zimbabwe) in 1987, the health district has become the keystone of African health systems. In order to break with the former centralised system and set up community health care programmes, national territories have been divided into health districts designed to guide patient through the coordinated care programme. The application of administrative standards has made it impossible to take into account mobility among the city population as well as the choices made by the individuals.In the cities, reality is very different since the use of health care according to geographical criteria does not necessarily match these conceptual boundaries. The health map of Ouagadougou has been draw using the pre-existing administrative boundaries to define health districts and the areas of responsibility of each health centre. Yet these areas rarely match the actual attractive areas for the same centres. The study of attractive areas makes it possible to determine to what extent limits are respected and how important is the location of a health centre in the city while searching for other relevant factors in defining areas of responsibility.